2016
DOI: 10.1183/13993003.00819-2015
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with right heart thrombi: the Right Heart Thrombi European Registry

Abstract: Our aim was the assessment of the prognostic significance of right heart thrombi (RiHT) and their characteristics in pulmonary embolism in relation to established prognostic factors.138 patients (69 females) aged (mean±SD) 62±19 years with RiHT were included into a multicenter registry. A control group of 276 patients without RiHT was created by propensity scoring from a cohort of 963 contemporary patients. The primary end-point was 30-day pulmonary embolism-related mortality; the secondary end-point included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 14 publications
6
90
1
3
Order By: Relevance
“…Previous studies did not report detailed data on the clinical condition of patients treated surgically, so perhaps this treatment was used in critically ill patients, which might explain high mortality associated with surgical treatment. This increase in mortality is also in contrast with the RIHTER registry data which showed a trend towards greater survival in patients treated invasively [7]. Thus, the safety of invasive treatment has not been clearly established but this therapy should be undertaken in patients with RiHT and PFO.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Previous studies did not report detailed data on the clinical condition of patients treated surgically, so perhaps this treatment was used in critically ill patients, which might explain high mortality associated with surgical treatment. This increase in mortality is also in contrast with the RIHTER registry data which showed a trend towards greater survival in patients treated invasively [7]. Thus, the safety of invasive treatment has not been clearly established but this therapy should be undertaken in patients with RiHT and PFO.…”
Section: Discussioncontrasting
confidence: 51%
“…For the same reason, it is controversial whether RiHT is an independent risk factor of early mortality. The RIHTER registry was an attempt to determine the effect of RiHT on treatment outcomes in patients with acute PE [7]. Data on 138 patients with RiHT were compared th day without RiHT (resolution at day 8), in an improved condition F -female; PE -pulmonary embolism; SBP -systolic blood pressure; HR -heart rate; SI -stroke index [HR/SBP]; rt-PA -recombinant tissue plasminogen activator; HIT -heparin-induced thrombocytopenia; M -male; TEE -transesophageal echocardiography; PFO -patent foramen ovale; BMI -body mass index; MEN I -multiple endocrine neoplasia type 1; LMWH -low-molecular-weight heparin; UFH -unfractionated heparin; VKA -vitamin K antagonist; eGFR -estimated glomerular filtration rate; CNS -central nervous system; NYHA -New York Heart Association; LVEF -left ventricular ejection fraction with a control group that included 276 patients with acute PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prognosis assessment is very important for therapeutic options and approaches in patients with pulmonary thromboembolism. Several studies reported that patients with RHT and PE had worse prognoses than control groups [60,61]. The International Cooperative Pulmonary Embolism Registry demonstrated that among patients with acute pulmonary thromboembolism, RHT was a marker of worse prognosis in initially apparently stable patients treated with heparin alone [61].…”
Section: A B Cmentioning
confidence: 99%